2013
DOI: 10.5194/gi-2-41-2013
|View full text |Cite
|
Sign up to set email alerts
|

Development of stroboscopic muography

Abstract: Abstract.Conventional muon radiography has concentrated on non-destructive studies of stationary objects with relatively long exposure times required to achieve sufficient muon statistics. A muon detection system with real time readings and a high spatial resolution detector, enables the investigation of dynamic processes in a stroboscopic mode, where image frames are synchronized with the phases of the dynamic target. Although the natural cosmic ray muon flux is quite low for imaging a rapid process, repetiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The result is a pattern of the contrast in the density distribution inside the objects, which is projected onto a 2-dimensional plane. Muography has been applied to the imaging of the internal structure of volcanoes (Tanaka et al, 2007(Tanaka et al, , 2009(Tanaka et al, , 2014Lesparre et al, 2012;Oláh et al, 2019), cultural heritage sites, including the Giza pyramids (Cheops and Chephren), Egypt, the Prambanan temples, Indonesia, Mount Echia, Italy, and Santa Maria del Fiore, Italy (Alvarez et al, 1970;Hanazato and Tanaka, 2016;Tanaka and Ohshiro, 2016;Morishima et al, 2017;Guardincerri et al, 2018;Cimmino et al 2019), industrial plants (Tanaka, 2013), and other natural (Tanaka et al, 2011;Oláh et al, 2012;Schouten, 2018) and man-made structures (Mahon et al, 2018). Prior works have focused on searching for undiscovered chambers or the total weight of the heritage site.…”
Section: Introductionmentioning
confidence: 99%
“…The result is a pattern of the contrast in the density distribution inside the objects, which is projected onto a 2-dimensional plane. Muography has been applied to the imaging of the internal structure of volcanoes (Tanaka et al, 2007(Tanaka et al, , 2009(Tanaka et al, , 2014Lesparre et al, 2012;Oláh et al, 2019), cultural heritage sites, including the Giza pyramids (Cheops and Chephren), Egypt, the Prambanan temples, Indonesia, Mount Echia, Italy, and Santa Maria del Fiore, Italy (Alvarez et al, 1970;Hanazato and Tanaka, 2016;Tanaka and Ohshiro, 2016;Morishima et al, 2017;Guardincerri et al, 2018;Cimmino et al 2019), industrial plants (Tanaka, 2013), and other natural (Tanaka et al, 2011;Oláh et al, 2012;Schouten, 2018) and man-made structures (Mahon et al, 2018). Prior works have focused on searching for undiscovered chambers or the total weight of the heritage site.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are limitations to the targetable size of the objects that can be imaged by muography, researchers have applied this technique to various scientific targets that include volcanoes [such as Asama, Japan [1][2][3], Satsuma-Iwojima, Japan [4,5], Showa-shinzan, Japan [6], Usu, Japan [7], Unzen, Japan [8], La Sourfiere, France [9,10], Puy de Dome, France [11], Stromboli, Italy [12] and Etna, Italy [13,14]], seismic faults in Japan [15,16], ancient architecture [such as the Egyptian pyramids [17][18][19], and Mt. Echia, Italy [20]], and industrial plants [including electric furnaces [21] and nuclear reactors [22]].…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing data collected during several months of operation, they concluded that areal density of the pyramid was measured with a precision of 2 % along the muon paths that penetrated over 100 m through limestone in the pyramid. This pioneering experiment was a crucial step that eventually led to recent muographic experiments that explored inside volcanoes (Tanaka et al, 2007(Tanaka et al, , 2008(Tanaka et al, , 2009Lesparre et al, 2012;Cârloganu et al, 2012;Carbone et al, 2013;Kusagaya and Tanaka, 2015a, b), industrial plants (Tanaka, 2013;Ambrosino et al, 2015), seismic faults (Tanaka et al, 2011;Tanaka, 2015), and caves (Caffau et al, 1997;Barnaföldi et al, 2012;Oláh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%